Shared territory: crossroads of languages, space for reflection - Corona, Marilice (PORTO ARTE: Revista de Artes Visuais, 2017)
Contemporary painters like Mark Tansey and Michaël Borremans include photography and film in their artistic practices, reflecting, in shared territory and in a self-referential style, the undeniable technological mediation in which we see ourselves submerged. This article aims to analyze, inside this crossroads of languages, how a space for reflection is established.